Humanos Indireitos?: Modos de Subjetivação de Adolescentes e Jovens a quem se atribui o cometimento de ato infracional. - Cavalcante, Clara Oliveira Barreto (2020)
Considerem the context of lethal violence and the upsurge of punitive devices that make black youth segments impoverished and made impoverished as "unworthy humans" invisible, this dissertation had the general objective of analyzing ways of subjectivating young people in the context of violence, from the narratives of subjects to whom it is attributed the practice of infracional act concerning their trajectories. The specific objectives were: 1) to discuss narratives of adolescents and young people who are responsible for committing an infraction on their youth experiences in peripheral territories and their crossings with art; 2) map the effects of the dynamics of violence on the daily lives of these adolescents and young people; 3) problematize public policy relations with these adolescents and young people, based on their institutional trajectories. Methodologically, it was a cartography as a research-inter (in) intervention method, linked to the extension project Histórias Desmedidas, carried out by VIESES: Research and Interventions Group on Violence, Social Exclusion and Subjectivity. Participants were subject to an open medium measure at the Specialized Social Assistance Reference Center (CREAS) of Regional V, in addition to graduates from the socio-educational system who participated in the actions of that extension project in said CREAS. The methodological strategies involved conducting thematic workshops, narrative interviews and monitoring of routes with participants in their territories and in the city. Participants' narratives about their youth experiences highlight scenes of rights violations, racism, violence and criminal subjection. Such narratives highlight experiences in a crossfire, due to the negative expectations of society about their futures, territorial conflicts linked to faction disputes and public security policies based on a logic of war and the manufacture of enemies. In fact, it corroborates the production of modes of (de) subjectivation from which death is currently lurking. The onslaught of mortification of such youths occurs not only due to their exposure to physical annihilation, but through a colonial matrix of power that symbolically engenders experiences of silence, erasure, homogenization, segregation, institutional abandonment, scarce citizenship and the absence of a perspective of prosperous and long-lived future. Institutional violence, expressed mainly in relation to the socio-educational system and the police, stands out in their narratives. Affections such as hatred, fear and resentment towards different institutions are highlighted. Insurgencies and re-existences are also noticeable in the narratives of these young people about themselves, either when they demonstrate non-conformity with the problem of precariousness in life, the violation of rights and daily exposure to violent death, or through the creation of strategies to singularize their lives, from, for example, the experimentation of displacements through a historically segregated city and the factionalized peripheral territories themselves, in addition to the incorporation of art, poetry and literature as devices for reinventing existential territories. Thus, such research can contribute to discussions about modes of subjectivation and resistance strategies in necropolitical times.